An overview of current knowledge concerning the inventory and sources of plutonium in the China Seas. (January 2020) - Wu, Junwen; Sun, Jiang; Xiao, Xiyu
Abstract: This study reviews the current understanding of the inventory and sources of plutonium (Pu) in the marine environment adjacent to China. The 239+240 Pu inventory in the China Seas was found to have large spatial variations. The quantity in sediments decreases away from the shore, generally tracing the sedimentation rate distribution. High 239+240 Pu inventories indicated that Pu in the water column was easily scavenged since Pu has a high particle affinity. Indeed, substantially higher 240 Pu/ 239 Pu atom ratios were observed in the sediment and seawater of the China Seas than are found in global fallout. We thus clarified that Pu sources in the China Seas were from both global fallout and the Pacific Proving Grounds (PPG) in the Pacific Marshall Islands. Plutonium from the latter source is transported into the China Seas through the North Equatorial Current (NEC) and Kuroshio. Using a two end-member mixing model, we revealed that the contribution of Pu from the PPG accounts for over 40% of the Pu in the East China Sea (ECS) and South China Sea (SCS), and less than 20% of the Pu in the Yellow Sea (YS). The distributions and isotopic composition of Pu in the China Seas indicate strong scavenging of Pu in the ECS and high Pu accumulation in the SCS. This information on the inventory and isotopic composition of Pu helps to establish a background for the future study of Pu in the China Seas. Highlights: Pu from the Pacific Proving Grounds continuously transported into the China Seas. Pu in the China Seas is sourced from global fallout and the Pacific Proving Grounds. Pu source largely determines its distribution and inventory within the China Seas. Pu is substantially scavenged in the East China Sea. Pu has high accumulation in the South China Sea.